Canadian business corporations law - McGuinness, Kevin Patrick (LexisNexis Canada Inc., 2023)
"This book provides comprehensive analysis of Canadian corporate law topics. The subjects covered in Volume 1 are foundational in nature: the corporate concept, corporate governance, historic foundations of corporate law, etc."– Provided by publisher.